2018
DOI: 10.1111/cas.13763
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibition of MEK and PI3K pathways overcomes acquired resistance to EGFR‐TKIs in non‐small cell lung cancer

Abstract: Compensatory activation of the signal transduction pathways is one of the major obstacles for the targeted therapy of non‐small cell lung cancer (NSCLC). Herein, we present the therapeutic strategy of combined targeted therapy against the MEK and phosphoinositide‐3 kinase (PI3K) pathways for acquired resistance to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) in NSCLC. We investigated the efficacy of combined trametinib plus taselisib therapy using experimentally established EGFR‐TK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 46 publications
0
44
1
Order By: Relevance
“…Investigating the mechanism revealed that inhibiting PDE4D restored tamoxifen sensitivity through induction of the unfolded protein response and subsequent activation of p38 and JNK. In lung cancer, blocking the downstream effectors MEK or PI3K is ineffective in overcoming resistance to EGFR inhibitors [142]. However, combined MEK and PI3K blockade successfully interfered with features of malignant transformation caused by drug-resistant EGFR mutants.…”
Section: The Role Of the P38 Pathway In Drug Sensitivitymentioning
confidence: 99%
“…Investigating the mechanism revealed that inhibiting PDE4D restored tamoxifen sensitivity through induction of the unfolded protein response and subsequent activation of p38 and JNK. In lung cancer, blocking the downstream effectors MEK or PI3K is ineffective in overcoming resistance to EGFR inhibitors [142]. However, combined MEK and PI3K blockade successfully interfered with features of malignant transformation caused by drug-resistant EGFR mutants.…”
Section: The Role Of the P38 Pathway In Drug Sensitivitymentioning
confidence: 99%
“…6 Another acquired resistance mechanism to EGFR-TKIs is up-regulation of the RAS/ RAF/MEK/ERK signaling pathway, key to cell survival and proliferation 7,8 ; this can occur downstream of various other signaling pathways. 9 Combination targeted therapy may overcome genomic heterogeneity of drug resistance. However, the risk of overlapping toxicities and resulting dose adjustments can impede effective combinations.…”
Section: Introductionmentioning
confidence: 99%
“… 19 The PI3K/Akt pathway is regarded as the primary pathway of cancer cell survival. 20 Inhibition of the EGFR/PI3K/Akt signaling pathway has been shown to suppress the survival and migration of NSCLC cell lines. 20 We confirmed that downregulation of miRNA-365 suppressed protein expression of NKX2-1 and induced expression of EGFR, PI3K, and p-Akt protein in vitro.…”
Section: Discussionmentioning
confidence: 99%